Prospective study of sentinel lymph node mapping for endometrial cancer. Issue 3 (19th September 2018) - Togami, Shinichi; Kawamura, Toshihiko; Fukuda, Mika; Yanazume, Shintaro; Kamio, Masaki; Kobayashi, Hiroaki
Abstract: Objective: To evaluate sentinel lymph node (SLN) mapping for endometrial cancer, using radioisotope and indocyanine green (ICG) injections. Methods: A prospective study was conducted between April 1, 2014, and December 27, 2017, among women with endometrial cancer, excluding those with suspected peritoneal dissemination and lymph node metastasis, at a University hospital in Kagoshima, Japan. Patients with low‐risk endometrial cancer underwent pelvic SLN mapping using uterine cervix radioisotope injections; intermediate/high‐risk patients underwent pelvic SLN with/without intraoperative para‐aortic SLN mapping with ICG subserosal injections. Primary endpoints were estimated detection rates, sensitivity, and negative predict values (NPV) of SLN mapping. Results: Of 113 patients evaluated, comprehensive pelvic lymphadenectomy was performed after SLN detection in all patients; additional para‐aortic lymphadenectomy was performed in 38 (34%) patients. The detection rates for pelvic SLN (≥1), bilateral pelvic SLN, and para‐aortic SLN (≥1) were 96%, 80%, and 55%, respectively. Pelvic and para‐aortic lymph node metastasis were found in (10%) (12/113) and 18% (6/33) patients, respectively. Isolated para‐aortic lymph node metastasis was not observed. In pelvic SLN analysis, sensitivity was 91% and NPV was 99%. In para‐aortic SLN analysis, sensitivity and NPV were 100%. Conclusion: SLN biopsy may be useful to avoid comprehensive pelvic lymphadenectomy in low‐risk patients. In high‐risk patients, SLN mapping revealed high detection rates, sensitivity, and NPV, including those for para‐aortic SLN. Abstract : Sentinel lymph node napping demonstrated high sensitivity and negative predictive value for pelvic and para‐aortic lymph node mapping metastasis among patients with endometrial cancer.